Differences in care delivery for children and adolescents with cancer in Europe – Results from the SIOPE OCEAN project - Maria Otth; Teresa de Rojas; Kerstin K. Rauwolf; Miguel Martins; Uta Dirksen; Delphine Heenen; Lejla Kameric; Pamela Kearns; Ruth Ladenstein; Cormac Owens; Caroline Queiroz; Richard Sullivan; et al. (EJC Paediatric Oncology)
Background: Variations in access to high quality clinical care and research are global issues for children and adolescents with cancer. Therefore, SIOPE launched the OCEAN project (Organisation of Care and rEsearchfor children with cANcer in Europe) to map the landscape for both these domains. Here we present the clinical care part. Methods: We used a mixed methods approach to map epidemiological data and self-reported care aspects. We described cancer incidence in children and adolescents aged 0–24 years. For the qualitative part, we performed a survey covering a broad range of care aspects. We used descriptive statistics to present the results. Results: The cancer incidence across Europe was 15/100’000 and 26/100’000 in those aged 0–14 and 15–24 years respectively in 2022. Representatives from 37 countries responded to the survey. These countries cover 385 centres treating cancer in children and adolescents, including 18 cancer centres. Highly specialized treatment modalities and care structures are not available in every country. Public health insurances reimburse standard of care treatments in most countries (35/37); however, they do not cover all costs and additional funding is reported to be needed in up to one fifth of countries. Discussion: Differences exist in many aspects of clinical care of the 37 countries, but the key aspects are delivered in all countries. We interpret that highly specialised diagnostic tools and treatment modalities must be concentrated in selected centres. A well-functioning national and international collaboration must be guaranteed to give all children and adolescents with cancer equal access to best clinical care.